Global burden of pancreatitis among individuals aged 15–39 years: a systematic analysis from the 2021 GBD study - Xu, Biwu; Li, Kaiyuan; Liu, Peng (Frontiers in Medicine, 2025)
BackgroundPancreatitis represents a significant global public health challenge, yet there is a lack of comprehensive analyses focusing on the burden of pancreatitis and its long-term trends among young individuals aged 15–39 years.MethodsThis study utilized data from the Global Burden of Disease (GBD 2021) database to analyze the prevalence, incidence, and disability-adjusted life years (DALYs) associated with pancreatitis in the 15–39 age group from 1990 to 2021. Temporal trends in disease burden were assessed by calculating the estimated annual percentage change (EAPC), with point estimates and their 95% uncertainty intervals (UIs) reported.ResultsBetween 1990 and 2021, the global number of cases related to pancreatitis—including prevalence, incidence, DALYs, and deaths—substantially increased in the 15–39 age group. However, age-standardized rates for prevalence, incidence, DALYs, and mortality showed a declining trend. Gender-specific analysis revealed that females had lower prevalence and incidence rates compared to males. Socio-demographic Index (SDI)-based subgroup analysis indicated that low-SDI regions experienced the largest increases in DALYs and deaths, while high-SDI regions showed the most significant declines in age-standardized DALYs and mortality rates. Geographically, East Asia demonstrated the largest decrease in the burden of pancreatitis, whereas Western Sub-Saharan Africa exhibited the highest increases in case numbers and deaths. Age-stratified analysis showed that individuals aged 35–39 years had the greatest increases in case numbers and disease burden, despite experiencing the most notable decline in incidence rates. Conversely, the 15–19 age group exhibited reductions in disease burden and mortality rates.ConclusionThis study highlights that, while the global number of pancreatitis cases among young individuals aged 15–39 has risen from 1990 to 2021, the overall disease burden has declined, particularly in high-income regions. In contrast, the disease burden in low-income regions continues to rise.